The Craft of University Teaching - Lindsay, Peter, 1958- (Book collections on Project MUSE., 2018)
The Craft of University Teaching makes the case for a craft perspective on university teaching. In making this case, it examines what university teaching looks like when viewed under the lens of craftwork.